ANALISIS KEBIJAKAN DAN KOMPETENSI PEMIMPIN RUMAH SAKIT DI INDONESIA: HARUSKAH TENAGA MEDIS? (SUATU STUDI LITERATUR) - dr. Ira Citra Afsari, MMRSa; dr. Albert Hendarta, MPHb; Roma Ave Maria Ave (Jurnal Kesehatan, 2023)
Based on UU No.44/2009 and Permenkes No.147/Menkes/PER/I/2010 it allows hospitals not only to function socially but also in the form of a Limited Liability Company (private company) as a 'stand alone' hospital or in the form of a 'chain hospital' which is socially profitable cause a competition between hospitals. Hospitals need to be managed more professional, need strong leadership, long experience and must play an active role to make health services run perfectly. Design of this reasearch is a literature review, used some literature about hospital leadership, health workers, hospital. It was found that government policy of Indonesia still requires medical personnel to hold the positions as directors of hospitals. There is no possibility of non-health workers even though they have above average abilities as a leader. In contrast to hospital leaders outside Indonesia, although more advanced for scientifically and technologically that position can be filled by an accountant, businessman, public health, even by a specialist doctor even though the medical director always from medical personnel who have knowledge in accordance with their competence. Indonesia policies related to hospital leaders must be supported by educational institutions, they need in addition to having knowledge and qualified medical service skills, a medical staff must have other knowledge and abilities such as leadership, financial literacy, management and entrepreneurial leadership, entrepreneurship, strategic business plans, strategic action plans, implementation plans and annual plans, hospital governance, minimum service standards, accountability systems, hospital remuneration systems, human resource management. A health worker must also have the characteristics of a hospital leader, including: a hospital leader should have a vision, a hospital leader should be a good manager, a hospital leader should be communicative, humble and enthusiastic, a hospital leader should manage the hospital by going around, a hospital leader should be professional, a hospital leader should understand change management, a hospital leader should have a service culture. A hospital leader should be aware of his core tasks. Leaders in hospitals must also inspire vision, set an example, show the way, empower, involve, challenge and challenge the process and humanize or touch the hearts of those who are led.